Relationship the Availability of Infrastructure and the Behavior of Preventing Covid-19 in Indonesia - Bayu Yoni Setyo Nugroho; Fitria Dewi Puspita Anggraini; Supriyono Asfawi; Achmad Binadja (Institute of Computer Science (IOCS), 2022)
The availability of infrastructure and the use of its in public have become the norm around the world since the outbreak of the 2019 coronavirus (COVID-19) pandemic. This study aims to determine the relationship between the availability of infrastructure and behavior of preventing Covid-19. Quantitative research with descriptive correlation design using a cross sectional approach. The independent variable in this study is the availability of infrastructure with the dependent variable being the Covid-19 prevention behavior. Data collection was carried out directly through the online method using Kobotoolbox. The sample in this study were residents of the community around the student's residence who were able to read and write and were willing to become respondents with a total of 2,700 respondents. The data obtained were tested for normality first by looking at the significance value on the results of the Kolmogorof Smirnov data normality test. Furthermore, the bivariate test was carried out using the Spearman Rank test. Bivariate test using Spearman's Rank Test between the variables of access to infrastructure and prevention behavior obtained the results of 0.272 with a p value of 0.000 (p value <0.05), with a correlation coefficient that is significant. very strong/perfect. There is a relationship between the availability of infrastructure and Covid-19 prevention behavior. The public must always pay attention to health protocols as an effort to prevent Covid-19.